Large volume spacer devices and the influence of high dose beclomethasone dipropionate on hypothalamo-pituitary-adrenal axis function. - Brown, P H (1993)
BACKGROUND: The systemic effects of the inhaled corticosteroid beclomethasone dipropionate are reduced if the drug is inhaled through a large volume spacer. Use of spacers may therefore permit higher doses to be given without causing hypothalamo-pituitary-adrenal suppression. METHODS: Randomised, double blind, double dummy, parallel group study was carried out in adults with chronic asthma to determine the dose of beclomethasone dipropionate causing hypothalamo-pituitary-adrenal suppression when the drug was administered by metered dose aerosol with and without a large volume spacer. After a four week run in taking 1.5 mg beclomethasone daily 50 patients underwent tests of hypothalamo-pituitary-adrenal function (measurement of 0900 h serum cortisol concentration and 24 hour urinary free cortisol excretion and the short tetracosactrin test). Six patients had hypothalamo-pituitary-adrenal suppression (results of at least two tests subnormal) and asthma was well controlled in six others. Thirty eight patients received increasing doses of beclomethasone with (group S) or without (group MDI) a 750 ml spacer. The daily dose was increased by 0.5 mg at monthly intervals until hypothalamo-pituitary-adrenal suppression developed or a dose of 5 mg/day was achieved. Asthma symptoms and peak expiratory flow were recorded daily. RESULTS: Twenty three patients completed the study, one (group S) reaching a dose of 5 mg beclomethasone dipropionate daily without hypothalamo-pituitary-adrenal suppression. Reasons for withdrawal were poor compliance (n = 10), the patient's decision (n = 3), and asthma that was too unstable (n = 2). "Intention to treat" analysis showed that the median dose of beclomethasone causing hypothalamo-pituitary-adrenal suppression was similar in the two groups (3.25 mg in S v 3.0 mg in MDI; 95% confidence interval (CI) for difference -1.0 to 1.0 mg). At 2 mg/day of beclomethasone most patients in both groups had well controlled asthma and there were no differences in symptoms or peak flow between the groups. Good control at this dose did not permit conclusions to be drawn about the efficacy of higher doses. CONCLUSIONS: There is wide interindividual variation in the dose of beclomethasone dipropionate causing hypothalamo-pituitary-adrenal suppression. Whether or not a spacer is used, doses higher than the currently accepted maximum of 2 mg/day can be taken by many adults with asthma without causing subnormal function of the hypothalamo-pituitary-adrenal axis. Whether these higher doses are more effective in controlling asthma remains to be established.